2009
DOI: 10.1158/1535-7163.mct-08-0848
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin (ET-743) promotes differentiation in myxoid liposarcoma tumors

Abstract: Differentiation is a complex set of events that can be blocked by rearrangements of regulatory genes producing fusion proteins with altered properties. In the case of myxoid liposarcoma (MLS) tumors, the causative abnormality is a fusion between the CHOP transcription factor and the FUS or EWS genes. CHOP belongs to and is a negative regulator of the large CAAT/enhancer binding protein family whose A, B,and D members are master genes of adipogenesis. Recent clinical data indicate a peculiar sensitivity of thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
147
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 161 publications
(154 citation statements)
references
References 32 publications
5
147
1
1
Order By: Relevance
“…Preliminary studies have suggested that myxoid liposarcomas with type I FUS-CHOP chimeric transcript may respond better to trabectedin. 37,38 Although the role of chimeric transcript type and variants have not been established in clear cell sarcoma, future studies or new therapeutic approaches may be revealing.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have suggested that myxoid liposarcomas with type I FUS-CHOP chimeric transcript may respond better to trabectedin. 37,38 Although the role of chimeric transcript type and variants have not been established in clear cell sarcoma, future studies or new therapeutic approaches may be revealing.…”
Section: Discussionmentioning
confidence: 99%
“…One variant may be more aggressive than the others, or may respond better to chemotherapy such as trabectedin. 2,12,15,16 As newer chemotherapeutic and other treatment strategies are developed for myxoid liposarcoma, confirmation of both the diagnosis and subtyping of the translocation may become part of routine clinical practice and of future research studies to identify the best treatment for each patient in this era of personalized medicine. In conclusion, we have developed a clinically robust RT-PCR assay that can identify and determine all known breakpoints in the most common subtypes of myxoid liposarcoma, and have identified a new FUS-DDIT3 mRNA breakpoint, which needs to be considered in future myxoid liposarcoma studies.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, an in vitro study of the drug on myxoid liposarcoma cell lines showed that treatment with trabectedin lead to dissociation of the FUS-DDIT3 protein product from chromatin and promotes gene expression consistent with terminal adipogenesis, but this response was only seen in the cell lines with the type 1 FUS-DDIT3 fusion and not in a cell line with the rarer type 8 gene fusion. 16 Of note, both the type 3 and type 8 gene fusions have more of the RNAbinding domain from FUS included in the gene fusion. Although these data are incomplete, it suggests that as new therapies are developed, the specific gene fusion type may become relevant, which highlights the need for assays that can differentiate the gene fusion type in the clinical setting.…”
mentioning
confidence: 99%
“…Moreover, trabectedin treatment was associated with significant histopathologic changes, characterized by regression of the capillary network and a presence of mature lipoblasts. A possible explanation for these changes could be that, by blocking the trans-activating ability of FUS-CHOP chimeric protein, trabectedin might modulate the transcription of genes that are crucial for adipocytic differentiation (28). The findings observed in myxoid liposarcoma could also be extrapolated to other sarcomas in which the translocation results in an altered regulation of the expression of transcription factors.…”
Section: Mechanism Of Action In Specific Subtypes Of Sarcomasmentioning
confidence: 99%